2009
DOI: 10.1007/s11665-008-9304-7
|View full text |Cite
|
Sign up to set email alerts
|

Texture Evolution in a Warm-Rolled Ti-IF Steel During Cold Rolling and Annealing

Abstract: The texture characteristics of a Ti-IF steel in ferritic hot-rolled (warm-rolled), cold-rolled, and annealed status were studied. The hot bands were obtained by finish rolling in ferrite region, coiling at very low temperature, and then directly annealing in industrial trial. It was found that 001 f g 110 h i dominates at the surface and 111 f g 112 h iis the main component at the midsection in the hot band. The α-fiber at the surface as well as at the midsection intensifies during cold rolling and weakens dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Jonas [7] reported that warm rolling has gained in popularity among steelmakers as a means of cutting the cost of steel production and opening up the window of hot band properties. Guan et al [8], Guo et al [9], and Wang et al [10] have reported similar findings using warm rolling. Warm rolling also has an advantage in that beneficial textures can be developed to improve deep drawability, especially in the production of warm-rolled IF steel [11,12].…”
Section: Introductionmentioning
confidence: 61%
“…Jonas [7] reported that warm rolling has gained in popularity among steelmakers as a means of cutting the cost of steel production and opening up the window of hot band properties. Guan et al [8], Guo et al [9], and Wang et al [10] have reported similar findings using warm rolling. Warm rolling also has an advantage in that beneficial textures can be developed to improve deep drawability, especially in the production of warm-rolled IF steel [11,12].…”
Section: Introductionmentioning
confidence: 61%
“…% C. It was found that the 0.016 wt. % C sample had a microstructure of as-casted ferrite grain of ultra low carbon steel [13][14][15]. As seen in Figure 6b, the grain size is smaller and more homogenuous owing to rolling and annealing processes.…”
Section: Resultsmentioning
confidence: 99%
“…Present results are also in agreement with the previous work [19] from laboratory experiments that the lowering finishing temperature improves the deformation texture with an increasing amount of {111} oriented grains which supports the formation of a sharper {111} recrystallised texture after coiling. Alpha orientation rotates to gamma orientation, leading to a high intensity of gamma fibre texture during cold rolling and therefore FR1 sample having relatively higher alpha fibre is expected to yield higher gamma fibre before annealing.…”
Section: Comparison Of Austenitic and Ferritic Rolled Coilsmentioning
confidence: 99%